Comparison of patients with avian influenza A (H7N9) and influenza A (H1N1) complicated by acute respiratory distress syndrome - Li, Hongyan (Medicine (Baltimore), 2018)
The aim of this study was to compare the clinical features of patients with avian influenza A (H7N9) and influenza A (H1N1) complicated by acute respiratory distress syndrome (ARDS). The clinical data of 18 cases of H7N9 and 26 cases of H1N1 with ARDS were collected and compared in the respiratory intensive care unit (RICU) of Fuzhou Pulmonary Hospital of Fujian from March 2014 to December 2016. Patients with H7N9 had a higher acute physiology and chronic health evaluation-II score (P < .05) and lung injury score (P < .05). The rates of coexisting diabetes mellitus, hyperpyrexia, and bloody sputum production were significantly higher in the H7N9 group than in the H1N1 group (P < .05). The H7N9 group had a longer duration of viral shedding from the onset of illness (P < .05) and from the initiation of antiviral therapy (P < .05) to a negative viral test result than the H1N1 group. Patients with H7N9 had higher rates of invasive mechanical ventilation; serious complications, including alimentary tract hemorrhage, pneumothorax or septum emphysema, hospital-acquired pneumonia (HAP) and multiple organ dysfunction syndrome (MODS); and hospital mortality (P < .05). At the 6th month of follow-up, the rates of bronchiectasia, reticular opacities, fibrous stripes, and patchy opacities on chest computed tomography (CT) were significantly higher in the H7N9 group than in the H1N1 group (P < .05). Based on multiple logistic regression analysis, H7N9 influenza viral infection was associated with a higher risk of the presence of severe ARDS than H1N1 influenza viral infection (odds ratio 8.29, 95% confidence interval [CI] 1.53–44.94; P < .05). Compared to patients with H1N1, patients with H7N9 complicated by ARDS had much more severe disease. During long-term follow-up, more changes in pulmonary fibrosis were observed in patients with H7N9 than in patients with H1N1 during the convalescent stage.